Interview with Professor Karen Vintges - Sapere Aude, Revista (Sapere Aude, 2013)
Interview with Professor Karen Vintges. She is a University Lecturer in Political and Social Philosophy in the Department of Philosophy at the University of Amsterdam, Netherlands. Coordinator of the NWO program ‘Women and Islam: New Perspectives’, and currently works on a project entitled Rewriting The Second Sex From a Global Perspective.